Bacterial zoonotic diseases awareness for poultry traders at Sukahaji Bird Market as an one health implementation [Penyadartahuan penyakit zoonotik bakterial pada pedagang unggas di Pasar Burung Sukahaji sebagai upaya penerapan one health] - Faisal Amri Satrio; Vincentius Owen Chen; Hana Nayla Rahma; Alysa Gema Fatiah Putri; Haitsam Muhammad Hilmi; Nadiyah Dwi Prianti; Nasywa Nadila; Sarasati Windria; Wendi Prameswari; Yumni Khairina Ghassani (Buletin Pengabdian Bulletin of Community Services, 2025)
Zoonotic bacterial diseases such as colibacillosis and salmonellosis in poultry affect animal health and productivity and pose a risk to human health. Sukahaji Bird Market in Bandung City is a high-traffic site for live poultry trading and close human-animal interaction, making it a potential hotspot for zoonotic disease transmission. This work aimed to improve poultry traders' knowledge on the bacterial zoonotic diseases and promote the application of basic biosecurity measures as a preventive effort. In this work, implementing methods involved three main stages namely pre-activity, main activity, and post-activity. The pre-activity stage involved coordinating with the market managers and institution partners, developing simple surveys, and preparing the educational materials (pamphlets and posters). The main activity was conducted through an interactive education approach, distribution of printed materials, survey completion, and the provision of hand sanitizer to support the hygiene practices. In the post-activity stage, the evaluation process was carried out throughout surviving 30 poultry traders to assess their knowledge, attitudes, and practices related to biosecurity. Results showed that 96.67% of traders were not aware of bacterial zoonotic diseases in poultry, while 93.3% were able to recognize clinical signs of sick birds. Furthermore, although most traders had implemented basic hygienic practices, their understanding of zoonotic diseases remained limited. Both printed educational media and the personalized approach have an effectiveness in enhancing awareness. Moreover, applying the community engagement activities could support the One Health strategy through integrating animal, human, and environmental approaches to control the zoonotic disease transmission in the traditional markets.